(3TQM GdebGeGJ GdMQjQjIs - (3eXgQ GdOjf MSjf MSf Hf eMehO Hf GdMSf GdRjOGfi(B( (3GdRHOGfi(B) (3GdVQjQ GdTjQGRis; (3GdMQjQj,J (B516 (3g` s ((3TgGH GdcQejfi s)
(3ChdgG (B:s
(3CeG HYO abO GbJQM hCdM Ydi ReQI ENhGfi hKdI NdGfi Cf CTQM dge cJGH GdebGeGJ GdPi ENJQYgG GdMQjQi s
(3BNQgG (B:s
(3hhdi GdNjQGJ Ci UGMH GdNjQGJ Ci efg GdNjQGJ jYfi gh eYWi cd NjQ ai GdOfjG hGdCNQI s
(3HChdgG Jedc dYHO GdQMef Hf Ydi Hf eDjO ai GdbSWfWjfjI SfI (B907 (3g` hCNQ dESMGb GdeOYh HedGLb RGOI SfI (B1153(3g`s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs